2020
DOI: 10.1101/2020.11.11.20230243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Early Assessment of Curfew and Second COVID-19 Lock-down on Virus Propagation in France

Abstract: This note provides an early assessment of the reinforced measures to curb the COVID-19 pandemic in France, which include a curfew of selected areas and culminate in a second COVID-19-related lock-down that started on October 30, 2020 and is still ongoing. We analyse the change in virus propagation across age groups and across départements using an acceleration index introduced in Baunez et al. (2020). We find that while the pandemic is still in the acceleration regime, acceleration decreased notably with curfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 3 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…One study reported that compliance with malaria chemoprophylaxis among soldiers during missions in Africa was negatively associated with eveningness chronotype (OR = 0.68) (Resseguier et al, 2010). Another study found that nighttime curfew indeed decreased the acceleration of the new coronavirus propagation, but mostly among the older population and not among the youngest individuals (up to 19 years old), and not as much as the full lockdown (Baunez et al, 2020). Future studies should directly test the eveningness epidemiological liability hypothesis using correlational and mediational approaches and disentangling the effects of eveningness chronotype from those of sex and age, and potentially even those of fast life history strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that compliance with malaria chemoprophylaxis among soldiers during missions in Africa was negatively associated with eveningness chronotype (OR = 0.68) (Resseguier et al, 2010). Another study found that nighttime curfew indeed decreased the acceleration of the new coronavirus propagation, but mostly among the older population and not among the youngest individuals (up to 19 years old), and not as much as the full lockdown (Baunez et al, 2020). Future studies should directly test the eveningness epidemiological liability hypothesis using correlational and mediational approaches and disentangling the effects of eveningness chronotype from those of sex and age, and potentially even those of fast life history strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Independently, Brauner et al (2020) did a similar worldwide analysis and concluded that closing some businesses such as restaurants, bars, nightclubs, cinemas, and gyms had a moderate-to-small effect in reducing COVID-19 transmission, indicating a promising policy option together with limiting gatherings to 10 people or less, which exhibited a large effect in reducing COVID-19 transmission. In France, nighttime curfew indeed decreased the acceleration of SARS-CoV-2 transmission, but the subsequent lockdown was more effective ( Baunez et al, 2020 ). Hence, it seems that a night-time shutdown would indeed inhibit COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The left-hand side, using official data from Santé Publique France from mid-may up to June 13, shows a concave scatter plot: the pandemic was decelerating in France at that time, right after the end of the first national lock-down. But three months later, the scatter plot on the right-hand side shows a convex relationship between tests and cases: the pandemic accelerated, even beyond that date and ended in a second wave and lock-down as well as other restrictive measures, some of which are still on-going (Baunez et al 2020c). From this relationship between tests and cases, we can deduce an acceleration index.…”
Section: Acceleration and Deceleration Of Harmmentioning
confidence: 93%
“…In Baunez et al [4,5], we have introduced an alternative and novel measure of viral activity in the context of COVID-19 -the acceleration index. This measure considers the variation of cases relative to the variation of tests and thus it avoids the shortcomings mentioned above.…”
Section: Introductionmentioning
confidence: 99%